Culture and psychology - Matsumoto, David (Wadsworth Cengage Learning, 2013)
This field-leading book puts psychological theories and concepts into a cross-cultural framework that invites readers to discover, question, and ultimately, understand the relationship between culture and psychology through exploration of topics like changing gender roles, sexuality, self-esteem, aggression, personality, and mate selection. It all adds up to a book that will leave readers with a deeper, more complex understanding of the nature of culture, its relationship to psychological processes, and the differences and similarities between cultures in the increasingly globalized world.